Similar efficacy, safety, and immunogenicity of the biosimilar BI 695501 and adalimumab reference product in patients with moderate-to-severe chronic plaque psoriasis: results from the randomized Phase III VOLTAIRE-PSO study. (2nd January 2021) - Menter, Alan; Arenberger, Petr; Balser, Sigrid; Beissert, Stefan; Cauthen, Ashley; Czeloth, Niklas; Soung, Jennifer; Jazayeri, Sasha; Weisenseel, Peter; Jayadeva, Girish
ABSTRACT: Background : BI 695501 is an approved biosimilar to Humira® reference product (RP). Research design and methods : In this randomized Phase III trial (VOLTAIRE-PSO), patients with moderate-to-severe chronic plaque psoriasis received BI 695501 or adalimumab RP (24-week treatment). Primary efficacy endpoint: the proportion of patients with ≥75% reduction in Psoriasis Area and Severity Index (PASI 75) response at week 16 (±18% equivalence limits for two-sided 95% confidence interval between treatment groups). Safety, pharmacokinetics, and immunogenicity were also assessed. Results : Baseline characteristics were balanced between treated groups (BI 695501, n = 159; adalimumab RP, n = 158). PASI 75 response rates (full analysis set, n = 158; n = 157) were 68.2% (BI 695501) and 70.4% (adalimumab RP) at week 16 (95% CI: −14.4%, 8.7%), and 75.3% and 72.4%, at week 24, respectively. At week 24, 41.5% (BI 695501) and 44.9% (adalimumab RP) of treated patients had treatment-emergent adverse events (AEs), 3.1% and 4.4% had serious AEs, and 0.0% and 1.9% had AEs of special interest. Of treated patients, 75.3% (BI 695501) and 77.9% (adalimumab RP) were anti-drug antibody-positive. Conclusion : These data demonstrate equivalent efficacy and highly similar safety and immunogenicity between BI 695501 and adalimumab RP in patients with chronic plaque psoriasis. Study identifier : NCT02850965